Cooperação bilateral no combate à criminalidade organizada transnacional: uma análise das ações brasileiro- paraguaias nas regiões de fronteira - Medeiros, Juliana Leite de (2018)
The rise of transnational organized crime to the level of threat to international security has brought significant changes to States' strategies to combat the problem. Its diffuse and networked character, adapted to the new economic reality of the post-Cold War, requires the concatenation of state efforts to confront it, otherwise it will render fruitless any policy in this regard. Cooperation emerges as an important alternative to ensure more effective results. Brazil and Paraguay have a prominent role in the development of illegal transnational activities in the South American continent, and there is a dynamic of complementarity between supply and demand of illegal products and services. The border between both countries corresponds to the more traditional route of drug trafficking, arms trafficking and smuggling in South America, which is why Brazil and Paraguay have joined efforts to address the issue. This dissertation seeks to analyze how cooperation between Brazil and Paraguay develops to combat organized crime on the border between both countries. For this, a conceptual rescue of transnational organized crime is made, inserting the phenomenon in the perspective of transnational illicit markets, and its characterization in the Brazil-Paraguay border. Next, the institutional policies and the Brazilian public management in the theme are discussed. Finally, the initiatives undertaken in the border region, in terms of bilateral cooperation, in combating cross-border illicit activities, are observed from 1988 to 2017.